Getting to the heart of cardiovascular complications associated with inflammatory arthritis - Hong Shi; Brian H Annex (EMBO Molecular Medicine)
Inflammatory arthritis encompasses a group of autoimmune diseases, including rheumatoid arthritis (RA), psoriatic arthritis (PsA), and ankylosing spondylitis (AS) (Hammaker and Firestein, 2018). Although the exact etiology remains elusive, these conditions are thought to result from an overactive immune response to an unknown antigen, leading to joint pain, swelling, and deformity. Among these, RA is the most prevalent, affecting approximately 1% of the world’s population (Di Matteo et al, 2023). A hallmark of RA is its association with elevated rates of cardiovascular disease (CVD), which significantly increases morbidity and mortality and shortens patients’ life expectancy and quality of life (Semb et al, 2020). Although the prognosis for RA has improved markedly over the past two decades due to advanced treatment options, the lack of targeted therapies for CVD complications in RA patients remains a critical clinical challenge. Finally, guideline-based therapies for CVD are based on the etiology of the disease, which is hypertension or coronary artery disease. How well these therapies work in patients with cardiac complications of RA is incompletely understood.